Persepsi Petani Sayuran Dataran Tinggi terhadap Pupuk Organik di Kelurahan Rurukan Kecamatan Tomohon Timur - Jefianty O. Perangin-Angin; Oktavianus Porajouw; Johny A. Tuyuwale; Caroline B.D. Pakasi (COCOS, 2013)
ABSTRACTJefianty Oktaria Perangin - angin. Perceptions of the Highlands Vegetable FarmersOrganic Fertilizer in Rurukan Vilage Sub District East Tomohon. Under the guidanceOctavianus Porajouw as chairman, and Johnny A. Tuyuwale and Caroline B.D.Pakasi as members.The objective of the study is to determine perceptions of highland vegetable farmersto organic fertilizer. This study uses primary data and secondary data. The primary dataobtained through interviews with farmers based on a list of questions (questionnaire), whilethe secondary data obtained from the format of the report profiles the village, Village officeRurukan. Data analysis method used in this research is descriptive, by calculating theaverage score of each answer given by the respondent.The results was this study indicate that the perception of farmers on organicfertilizer in Sub Rurukan still not good. This is due to the high level of complexity to obtainorganic fertilizer, organic fertilizer is also less cumbersome than inorganic fertilizers, aswell as the selling prices of vegetables using organic fertilizer that was low also becausefarmers in Rurukan was not obtained organic vegetables certified.Based on these results, it can be concluded that highland vegetable farmers'perceptions towards organic fertilizers are still lacking, so many farmers are using organicfertilizers into reuse of inorganic fertilizers. Hence the need for further dissemination of thelocal government, to provide counseling about the benefits and advantages of the use oforganic fertilizers. The government should also pay more attention to the needs of farmersin the use of organic fertilizers, so that farmers can apply organic fertilizer at maximumlevel.